Development and validation of prediction formula of Wingate test peak power from force-velocity test in men soccer players - Nikolaidis, P.; Knechtle, B. (Frontiers in Psychology, 2021)
Peak power of the Wingate anaerobic test (WAnT), either in W (Ppeak) or in W.kg-1 (rPpeak), has been widely used to evaluate the performance of soccer players; however, its relationship with force-velocity (F-v) test (e.g., whether these tests can be used interchangeably) has received little scientific attention so far. The aim of this work was to develop and validate a prediction equation of Ppeak and rPpeak from F-v characteristics in male soccer players. Participants were 158 adult male soccer players (sport experience 11.4 ± 4.5 years, mean ± standard deviation, approximately five weekly training units, age 22.6 ± 3.9 years, body mass 74.8 ± 7.8 kg, and height 178.3 ± 7.8 cm) who performed both WAnT and F-v test. An experimental (EXP, n = 79) and a control group (CON, n = 79) were used for development and validation, respectively, of the prediction equation of Ppeak and rPpeak from F-v test. In EXP, Ppeak correlated very largely with body mass (r = 0.787), fat-free mass (r = 0.765), largely with maximal power of F-v test (Pmax; r = 0.639), body mass index (r = 0.603), height (r = 0.558), moderately with theoretical maximal force (F0; r = 0.481), percentage of body fat (r = 0.471), fat mass (r = 0.443, p < 0.001); rPpeak correlated with rPmax (largely; r = 0.596, p < 0.001), theoretical maximal velocity (v0; moderately; r = 0.341, p = 0.002), F0 (small magnitude; r = 0.280, p = 0.012), BF (r = -0.230, p = 0.042), and fat mass (r = -0.242, p = 0.032). Ppeak in EXP could be predicted using the formula "44.251 + 7.431 × body mass (kg) + 0.576 × Pmax (W) - 19.512 × F0" (R = 0.912, R2 = 0.833, standard error of estimate (SEE) = 42.616), and rPpeak from "3.148 + 0.218 × rPmax (W.kg-1) + v0 (rpm)" (R = 0.765, R2 = 0.585, SEE = 0.514). Applying these formulas in CON, no bias was observed between the actual and the predicted Ppeak (mean difference 2.5 ± 49.8 W; 95% CI, -8.7, 13.6; p = 0.661) and rPpeak (mean difference 0.05 ± 0.71 W.kg-1; 95% CI, -0.11, 0.21, p = 0.525). These findings provided indirect estimates of Ppeak of the WAnT, especially useful in periods when this test should not be applied considering the fatigue it causes; in this context, the F-v test can be considered as an alternative of exercise testing for estimating the average Ppeak of a group of soccer players rather than for predicting individual scores when the interindividual variation of performance is small.